Development of an AAV9-RNAi-mediated silencing strategy to abrogate TRPM4 expression in the adult heart - Medert, Rebekka; Jungmann, Andreas; Hildebrand, Staffan; Busch, Martin; Grimm, Dirk; Flockerzi, Veit; Müller, Oliver J.; Most, Patrick; Schumacher, Dagmar; Freichel, Marc (Pflügers Archiv, 2021)
The cation channel transient receptor potential melastatin 4 (TRPM4) is a calcium-activated non-selective cation channel and acts in cardiomyocytes as a negative modulator of the L-type Ca2+ influx. Global deletion of TRPM4 in the mouse led to increased cardiac contractility under β-adrenergic stimulation. Consequently, cardiomyocyte-specific inactivation of the TRPM4 function appears to be a promising strategy to improve cardiac contractility in heart failure patients. The aim of this study was to develop a gene therapy approach in mice that specifically silences the expression of TRPM4 in cardiomyocytes. First, short hairpin RNAmiR30 (shRNAmiR30) sequences against the TRPM4 mRNA were screened in vitro using lentiviral transduction for a stable expression of the shRNA cassettes. Western blot analysis identified three efficient shRNAmiR30 sequences out of six, which reduced the endogenous TRPM4 protein level by up to 90 ± 6%. Subsequently, the most efficient shRNAmiR30 sequences were delivered into cardiomyocytes of adult mice using adeno-associated virus serotype 9 (AAV9)-mediated gene transfer. Initially, the AAV9 vector particles were administered via the lateral tail vein, which resulted in a downregulation of TRPM4 by 46 ± 2%. Next, various optimization steps were carried out to improve knockdown efficiency in vivo. First, the design of the expression cassette was streamlined for integration in a self-complementary AAV vector backbone for a faster expression. Compared to the application via the lateral tail vein, intravenous application via the retro-orbital sinus has the advantage that the vector solution reaches the heart directly and in a high concentration, and eventually a TRPM4 knockdown efficiency of 90 ± 7% in the heart was accomplished by this approach. By optimization of the shRNAmiR30 constructs and expression cassette as well as the route of AAV9 vector application, a 90% reduction of TRPM4 expression was achieved in the adult mouse heart. In the future, AAV9-RNAi-mediated inactivation of TRPM4 could be a promising strategy to increase cardiac contractility in preclinical animal models of acute and chronic forms of cardiac contractile failure.